Peri-operative therapy for operable gastroesophageal adenocarcinoma: past, present and future. (16th May 2018) - Aggelis, V; Cunningham, D; Lordick, F; Smyth, E C
Abstract: Surgery represents the only chance of cure for patients with gastroesophageal adenocarcinoma; however, surgery alone does not cure most patients. Over the past decade, several multimodality adjunctive treatments have improved survival for patients with operable gastroesophageal adenocarcinoma who are undergoing surgical resection; these include peri-operative chemotherapy, neoadjuvant chemoradiotherapy, adjuvant chemotherapy and adjuvant chemoradiotherapy. More recently, the results of several large randomised trials are leading to a shift in the peri-operative treatment of gastroesophageal cancer, away from anthracycline-based and towards taxane-based chemotherapy regimens. Emerging data support an increased focus on patients who are at high risk for poor operative outcomes such as R1 resection, and on patients who are at high risk for relapse following surgery such as those with lymph node metastases (N1+). Future developments may include use of fluorodeoxyglucose-positron emission tomography to inform a switch to non-cross resistant chemotherapy pre-operatively and substitution of alternative treatments for chemotherapy in high risk post-operative node positive patients. Conversely, in molecularly selected subgroups such as microsatellite unstable gastroesophageal cancer, peri-operative or adjuvant chemotherapy may not be helpful, and treatments such as immunotherapy may be considered. In this review, the most up-to-date clinical trials and translational research in the field of operable gastroesophageal cancer are discussed; with a focus on how best to risk stratify patients with operable disease for peri-operative treatment plus surgery, and how novel therapies might be integrated into standard treatments in order to improve survival outcomes in this patient group.